2015
DOI: 10.1074/jbc.m114.628958
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-binding Proteins Interact with Comparative Gene Identification-58 Linking Lipolysis with Lipid Ligand Shuttling

Abstract: Background: A multiprotein complex designated as lipolysome degrades intracellular triglycerides and contains proteins such as adipose triglyceride lipase (Atgl) and its co-activator Cgi-58.Results: Cgi-58 interacts with fatty acid-binding proteins (Fabps), which impact Atgl-mediated lipolysis and lipid signaling.Conclusion: Fabps modulate Atgl-mediated TG hydrolysis and link lipolysis with intracellular lipid ligand shuttling.Significance: Novel mechanistic insights into the regulation of lipid catabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 65 publications
0
44
0
1
Order By: Relevance
“…These studies provide important clues into the structural determinants by which CGI-58 regulates lipase activity [26,27]. Another recent study also demonstrated that cytosolic fatty acid binding proteins (FABP) directly interact with CGI-58 within its helix-loop-helix cap region, and FABP-CGI-58 interactions facilitate ATGL-mediated lipolysis [28]. This FABP-CGI-58 interaction during active lipolysis may be important in shuttling fatty acid and acylglycerol lipolysis products away from the lipid droplet [28], which is clearly defective in CGI-58 deficient cells [46].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
See 2 more Smart Citations
“…These studies provide important clues into the structural determinants by which CGI-58 regulates lipase activity [26,27]. Another recent study also demonstrated that cytosolic fatty acid binding proteins (FABP) directly interact with CGI-58 within its helix-loop-helix cap region, and FABP-CGI-58 interactions facilitate ATGL-mediated lipolysis [28]. This FABP-CGI-58 interaction during active lipolysis may be important in shuttling fatty acid and acylglycerol lipolysis products away from the lipid droplet [28], which is clearly defective in CGI-58 deficient cells [46].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
“…Another recent study also demonstrated that cytosolic fatty acid binding proteins (FABP) directly interact with CGI-58 within its helix-loop-helix cap region, and FABP-CGI-58 interactions facilitate ATGL-mediated lipolysis [28]. This FABP-CGI-58 interaction during active lipolysis may be important in shuttling fatty acid and acylglycerol lipolysis products away from the lipid droplet [28], which is clearly defective in CGI-58 deficient cells [46]. In fact, there is evidence that the fatty acids released from the lipid droplet under FABP-CGI-58 facilitation, are then translocated by FABP to the nucleus to act as peroxisome proliferator-activated receptor (PPAR) ligands [28].…”
Section: The Role Of Cgi-58 In Adipose Tissue Lipolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, we showed that PA induces ER stress and autophagy at early stage while autophagy is gradually impaired due to the elevated expression of A-FABP and accompanied by a further enhanced ER stress and inflammation in macrophages after prolonged PA treatment. A-FABP can physically interact with, hormone sensitive lipase (HSL) and coactivator of adipose triglyceride lipase (ATGL), comparative gene identification-58 (CGI-58) to mediate lipolysis and lipid signaling5253, and peroxisome proliferator-activated receptor gamma (PPAR-γ) to regulate gene transcription54. A-FABP also promotes ubiquitination and degradation of PPAR-γ via direct interaction of the two proteins55.…”
Section: Discussionmentioning
confidence: 99%
“…[176] BMS309403 was used in as tudy that revealed that FABP4 interacts with CGI-58. [177] It was shown that 50 and the dual FABP4/FABP5 inhibitor 52 reduced plasma triglyceride and free FA levels in mice with DIO. However,n os ignificant change in insulin, glucose, or glucose tolerance was observed, thus indicating that the FABP4/5 inhibitors ameliorate dyslipidemia but not insulinr esistance in DIO mice.…”
Section: Fatty-acid-bindingp Roteins (Fabps)mentioning
confidence: 99%